Pollination and mating dynamics unveiled by orchard-wide pedigree reconstruction in Acacia crassicarpa - Gustavo Martins; Muhammad Yuliarto; Tisha Melia; Nathan Lakey; Jared Ordway; Evandro V. Tambarussi; Ross Whetten; Juan José Acosta; Gary Hodge (Tree Genetics & Genomes, 2025)

Screening clonally replicated Acacia mangium breeding populations for tolerance to Ceratocystis canker and wilt disease - Jeremy Todd Brawner; Sri Sunarti; Arif Nirsatmanto; Heru Indrayadi; Marthin Tarigan; Muhammad Yuliarto; Sri Rahayu; Eko Bhakti Hardiyanto; Morag Glen; Caroline Mohammed; Anto Rimbawanto (Tree Genetics & Genomes, 2022)
Three screening trials of clonally replicated Acacia mangium seedlings were evaluated for survival and lesion length following inoculation with locally collected strains of Ceratocystis in Indonesia. Tolerance in the population was low with 6.7% of the 1033 clones represented by more than 4 ramets surviving repeated inoculations. Differences in tolerance among populations were slight; however, populations with consistently higher survival and shorter lesion lengths were from Papua New Guinea rather than Queensland. Estimates of the proportion of the experimental variation attributable to differences among parents (heritability) were low to moderate for both survival and lesion length. Estimates of the proportion of the experimental variation that was attributable to differences among clones (repeatability) were greater but typically similar to the heritability estimates, indicating that initial improvements from selection will primarily be derived from identifying tolerant parents. While genetic correlations among experiments were positive, estimates could not exclude the existence of host–pathogen interactions. Two validation trials of the tolerant clones were assessed 9 months after establishment; these trials verified that one-third of the clones identified in the nursery screening were also tolerant to Ceratocystis in field trials. The experiments confirmed that nursery screening may be used to quickly focus efforts on parents that produce more tolerant progeny, screening additional seedlings to increase selection intensity rather than using clonal replication to increase accuracy would lead to greater improvements in tolerance and field trials are required to verify disease tolerance at later ages.

Genetic structure of an important widely distributed tropical forest tree, Shorea parvifolia, in Southeast Asia - Masato Ohtani; Naoki Tani; Saneyoshi Ueno; Kentaro Uchiyama; Toshiaki Kondo; Soon Leong Lee; Kevin Kit Siong Ng; Norwati Muhammad; Reiner Finkeldey; Oliver Gailing; Mohamad Na’iem; Sapto Indrioko; et al. (Tree Genetics & Genomes, 2021)

Rapidly evolving sex-specific sequences in Calamus travancoricus Bedd. ex. Becc. and Calamus nagbettai R.R.Fernald & Dey - Binoy Kurian; A.S. Hemanthakumar; Joemon Jacob; Muhammad Ali Noushad; K. K. Sabu (Tree Genetics & Genomes, 2018)

Identification of differentially expressed genes related to coloration in red/green mutant pear (Pyrus communis L.) - Jun Wu; Guang Zhao; Ya-Nan Yang; Wen-Quan Le; Muhammad Awais Khan; Shao-Ling Zhang; Chao Gu; Wen-Jiang Huang (Tree Genetics & Genomes, 2013)